International collaboration teaching with Universitas Muhammadiyah Malang (UMM), Indonesia / Rusnani Ab Latif … [et al.] - Ab Latif, Rusnani; Ismail, Wan Ismahanisa; Mohd Shahid, Nadiatul Syima; Prasetyo, Yoyok Bekti; Susanti, Heny Dwi (UiTM Global @ Office of International Affairs, 2024)
A memorandum of understanding is an agreement between two or more parties outlined in a formal document. It is not necessarily legally binding, which depends on the signatories' intent and the language in the agreement but signals the willingness of the parties to move forward with a contract. A memorandum of understanding, or MOU, is a nonbinding agreement that states each party's intentions to act, conduct a business transaction, or form a new partnership. This type of agreement may also be referred to as a letter of intent (LOI) or memorandum of agreement (MOA). MOA are legally binding documents and serve to formalize the understanding between the parties involved, providing a framework for cooperation and collaboration.